Food : the chemistry of its components - Coultate, T. P. [ (Tom P.)] (RSC paperbacks, 2009)
"As a source of detailed information on the chemistry of food this book is without equal. With a Foreword written by Heston Blumenthal the book investigates food components which are present in large amounts (carbohydrates, fats, proteins, minerals and water) and also those that occur in smaller amounts (colours, flavours, vitamins and preservatives). Food borne toxins, allergens, pesticide residues and other undesirables are also given detailed consideration. Attention is drawn to the nutritional and health significance of food components. This classic text has been extensively rewritten for its 5th edition to bring it right up to date and many new topics have been introduced."--Book jacket